Efektivitas Penggunaan Media Pembelajaran Edpuzzle Berbasis Video Terhadap Hasil Belajar Peserta Didik pada Materi Suhu dan Pemuaian - Muhammad Syarif Hidayat; Nana; Makiyah, Yanti Sofi (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2023)
After Covid 19, computer-based distance learning was opened, but based on a preliminary study in one of the Public High Schools in the Kuningan Regency area, it obtained 710 out of a maximum score of 1600 (low category). The research method uses a quasi experiment with a Pretest-Posttest Control Group Design approach. This research was conducted in January - February 2023 at Public High School. The research population was all class XI IPA of SMA Negeri, consisting of 6 classes with 213 students. The research sample was taken using a random cluster sampling technique as many as 2 classes out of 6 classes, namely class XI IPA 1 as the intervention group and Class XI IPA 2 as the control group. Data analysis techniques used the Chi Square test, Fisher's test, and T-test. The results of the calculation of the hypothesis test using the paired sample t-test with a significance level (α = 0.05) obtained tcount>t_table, namely 3,495>2,030. it can be concluded that there are differences in the effect of using video-based Edpuzzle learning media on student learning outcomes at Public High School.